ANALISIS PERFORMA PROTOKOL MQTT PADA SISTEM MONITORING GAS BERBAHAYA MENGGUNAKAN SENSOR MQ135 TERINTEGRASI ANDROID - Tunjung Genarsih; Nindayu Indrasari; Ardianto Syaifur Rohman; Sihmaulana Dwianto; Angga Dwinanda; Salsabila Liandra Putri; Qanitah Qanitah (Jurnal Media Elektro, 2026)
This study analyzes the performance of the Message Queuing Telemetry Transport (MQTT) protocol in a hazardous gas monitoring system using an MQ135 sensor and an ESP8266 NodeMCU microcontroller, integrated with a Flutter-based Android application. The monitored gases include CO, NO₂, CO₂, and SO₂, based on the threshold limits set by Permenaker No. 5 of 2018. The objective of this study is to evaluate MQTT Quality of Service (QoS) parameters, including delay, jitter, packet loss, and throughput, across three QoS levels (0, 1, and 2). Sensor validation was conducted using the Repeatability Test and Threshold Detection Test. The results show that the sensor demonstrates good reliability with CV values ranging from 1.92% to 3.78% and an average detection success rate of 98.9%. MQTT testing indicates that QoS 0 achieves the lowest delay (42.3 ms), jitter (3.12 ms), and zero packet loss, and the highest throughput (18.6 kbps). Additionally, the system provides real-time notification with an average response time below 500 ms. However, QoS 1 is identified as the optimal configuration, balancing delivery reliability and network efficiency for real-time laboratory safety monitoring systems